The Influence of the Gate Geometry on Selected Process Parameters in the High Pressure Die Casting Technology - Majernik, Jan; Gaspar, Stefan; Podaril, Martin; Kolinsky, Jan (Manufacturing Technology Journal, 2019)
The design of the gating system and the adjustment of the technological parameters of high pressure die casting are closely correlated. Correct connection of the gating system structure and technological parameters will be reflected in the final casting quality. Significant influence on the filling progress of a mold cavity has a gate and its geometry. Within the gate, the final increasing of melt flow velocity arises and determines the filling mode. The contribution is devoted to the influence of the gate height on selected technological parameters. The obtained data are being evaluated and on the basis of the experimental results assessment, the recommendations applicable in the foundry industry are being deduced.
Keywords: high pressure die casting; gate; technological parameters